Religious Extremism and Power Politics in Pakistan: A Conceptual Study - Ejaz, Zahra; Manzoor, Sumaira; Islam, Aiman (ACADEMIA International Journal for Social Sciences, 2026)
This Paper has explained the nature of religious extremism and its connection with power politics in the political culture of Pakistan. Extremism in general and religious extremism in particular has become prevalent challenge of contemporary age, and Pakistan is one of the most vulnerable countries in this regard. This study has framed in order to grasp the conceptual clarity of this looming large phenomenon. The trends of religious extremism and its connection with power politics in Pakistan has also discussed through the lens of realism paradigm. It result has drawn how extremists use religion for politics, the cause of Islam is mere slogan, and behind the curtain real motives are power and authority. This study has analyzed the above phenomenon through the lens of Realism, Rational Choice Theory and Cost-Benefit analysis. In real politik, the basic struggle is to pursue self-interest, and self-interest translated into the language of politics as quest for power. However, it has concluded in this literature, whenever extremist agenda upraised for religious cause, the real motives linked with power politics and self-interest instead of serving religion. The paradoxical political history of Pakistan is filled with contradictions, episodic alliance and non-alliance with religious extremists to pursue power politics in the realm of domestic and international politics which give rise to intolerance extremism, terrorism and radicalization in the society. The cost-benefit analysis has concluded the state has to pay heavy cost in term of sustain power within and outside the country.